Implementation Of Financial Report Preparation For Small And Medium Micro Enterprises (Msmes) (Survey in Sukajadi Village, Soreang District, Bandung Regency) - et. al., Rini Susiani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Financial reports are a solution to problems that often occur in Micro, Small, and Medium Enterprises (MSMEs), namely problems in financial management. This study aims to determine and analyze the practice of preparing financial statements at MSMEs in Sukajadi Village, Soreang District, Bandung Regency. This type of research is qualitative research. Sources of data were obtained through observations and interviews of 30 MSME players engaged in the apparel convection industry, snacks, and sponge sandals. The results showed that MSME actors had not made adequate financial reports, only recording transactions that often occurred in their business. This is due to a lack of educational background, limited knowledge of accounting, and socialization or training from the government or institutions in charge of MSMEs which are still not maximal so that the understanding of the importance of financial reports is still not understood by MSME actors.